A study on the synthesis and the optical properties of InP-based quantum dots - Ministro, José João Henrique (2014)
The aim of this work is the study of the optical properties of InP quantum dots (QDs) and the exploration of a new method for the synthesis of InP/CdS core-shell QDs. A multitude of research on colloidal QDs requires detailed knowledge of the relation between optical and structural properties, namely the sizing curve, the intrinsic absorption coefficient and the molar extinction coefficient. In this work, InP QDs were synthesized and structurally and optically characterized. The sizing curve was established from the average QD diameter, obtained by transmission electron microscopy, and the position of the first excitonic absorption peak. The intrinsic absorption coefficient and molar extinction coefficient were determined from quantitative elemental analysis and the absorbance of the nanocrystals at short wavelengths. We found that the intrinsic absorption coefficient is size-independent in this wavelength region and the molar extinction coefficient increases linearly with the QD volume. The focus of our study was then shifted to the fabrication of core-shell QD heterostructures, based on a recently reported method that used a more sustainable and much cheaper phosphorus precursor for the synthesis of high-quality InP/ZnS QDs. Using this procedure, we synthesized highly luminescent InP/CdS QDs and their emission could be tuned in the visible and near-infrared spectral regions. Furthermore, time-resolved photoluminescence measurements were performed on samples of InP/ZnS and InP/CdS QDs. We also report an exploratory study on the mechanism of formation of InP QDs with this new method. A thorough understanding of the reaction mechanism will enable a better control over the synthesis products and is potentially relevant for the fabrication of QDs consisting of other III-V semiconductors (e.g. GaP).